INTEREST OF SEMESTER 8 STUDENTS OF MAYJEN SUNGKONONO UNIVERSITY, FACULTY OF ECONOMICS, MOJOKERTO IN SPSS USING ONLINE METHODS IN THE PANDEMI OF COVID-19 - Solichah Solichah; Dwi Dewianawati; Erry Setiawan (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2023)
This study aims to determine the value of understanding material that is useful, most useful, memorable and most memorable, 8th semester students at Mayjen Sungkono University, Faculty of Economics who collaborated with Arena Statistics with online methods during the covid = 19 pandemic. The method used in this study is a quantitative method with a population in this study of students at Mayjen Sungkono University, Faculty of Economics with management and accounting study programs class of 2017 totaling 257 students. students have completed administration 3) students are in good health (not sick). Type of quantitative research, secondary data from the Statistics Arena on May 2 to May 23, 2021 in the form of a data analysis questionnaire: Satisfaction Index and Importance Performance Analysis. The results showed that the online learning method had 1) student attendance values of 97.1% who attended the training and 2.9% of students did not attend the SPSS training. 2) The value of understanding material that is useful is 35% of students admit that comprehensive linear regression material is useful, 24% for material uncovering secrets of T tests, 23% for instrument validity material and 12% for non-linear regression material 3) The value of understanding the material that is most useful is 65% of students admit that they understand the material that is considered the most useful, then 31% of students understand the material sufficiently and 4% of students admit that they really understand it. 4) The value of understanding material that is memorable is 30% for material A comprehensive linear regression, 27% for material revealing secrets of the T test, 16% for material validity management and 6% for non-linear regression material. 5) The value of understanding the material that is most memorable is 61% of students understand the material and the most memorable, 33% of students admit that they quite understand the material that is most memorable, 6% of students admit that they really understand the material that is most memorable.